Prevalence and Distribution of Endoparasites in Carnivorous Primates from Thrissur Zoological Garden - Jaya, M.; Sandra, K. J.; Aja, M.; Prasanth, C. B.; Brinesh, R.; Krishna, M. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
The animals selected for the endoparasitic observation are four species of carnivorous mammals specifically, Asiatic lion (Panthera leo persica), Bengal tiger (Panthera tigris tigris), Indian leopard (Panthera pardus fusca) and Indian jackal (Canis aureus indicus) that have been captivated in Thrissur zoo. By using direct smear inspection, conventional sedimentation, and flotation procedures, the faecal samples were subjected to a thorough routine parasitological study to determine the presence of parasite eggs and oocysts. The current analysis revealed that helminth and protozoan parasites infest four species of carnivorous mammals. Ancylostoma, Toxascaris leonina, Toxocara, Strongyle type and the trematode eggs of the species of Paragonimus as well as the coccidian genera Isospora of protozoa, were all observed to be abundant in the gastro intestinal tract of chosen mammals as a result of the study. By statistical analysis, according to the most recent observations it is noticed thatToxocara makes upon 25% of wild mammals, and any of the parasites infects 60% of wild mammals.